A Pilot Randomized Clinical Trial: Oral Miltefosine and Pentavalent Antimonials Associated With Pentoxifylline for the Treatment of American Tegumentary Leishmaniasis - Martins, Sofia Sales; Barroso, Daniel Holanda; Rodrigues, Bruna Côrtes; da Motta, Jorgeth de Oliveira Carneiro; Freire, Gustavo Subtil Magalhães; Pereira, Ledice Inácia de Araújo; Kurisky, Patrícia Shu; Gomes, Ciro Martins; Sampaio, Raimunda Nonata Ribeiro (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction American tegumentary leishmaniasis (ATL), which can present as either cutaneous (CL) or mucosal leishmaniasis (ML), is endemic in South America, and first-line antimonial treatments are known for their wide range of adverse effects (AEs). Growing reports of drug resistance increase the urgency of the need for better treatment options. The objective of this pilot clinical trial was to assess the efficacy of and AEs associated with the oral combination of miltefosine and pentoxifylline based on a post hoc analysis. Methods A pilot, randomized, open-label clinical trial was performed. The experimental group (M+P) received 50 mg twice a day (BID) miltefosine and 400 mg three times a day (TID) pentoxifylline, and the control group (A+P) received 20 mg Sb+V/kg/day intravenously and 400 mg TID pentoxifylline. Patients with ML received treatment for 28 days, and patients with CL received treatment for 20 days. Results Forty-three patients were included: 25 with ML and 18 with CL caused by L.(V.) braziliensis. AEs were more frequent in the A+P group (p=0.322), and there was a need for treatment interruption due to severe AEs (p=0.027). Patients with CL had a higher chance of achieving a cure (p=0.042) and a higher risk of AEs (p=0.033). There was no difference in the chance of a cure based on the treatment (p=0.058). Conclusion In this pilot randomized clinical trial, M+P treatment and A+P treatment yielded similar cure rates, and the former was associated with a lower risk of AEs. Future studies with more patients and longer follow-up are recommended.